Integrasi Qawā'id Fiqhiyyah dalam Reformasi Hukum Acara Perdata: Tantangan dan Peluang - Suriyadi; Hidayat, Taufik; Addarajat, M. Zakky; Ardi (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2025)
This article explores the potential integration of qawă id fiqhiyyah into the reform of civil procedural law in Indonesia. Within a legal system still largely influenced by colonial legacies. Islamic legal values often remain underrepresented, particularly in procedural aspects of litigation. This study aims to identify the challenges and opportunities in adopting these legal maxims as foundational principles of civil procedure. Using a qualitative approach based on literature review of classical Islamic jurisprudence and relevant statutory documents, the study finds that the main obstacles include the limited recognition of gawa id fighiyyah as independent legal sources, gaps in practitioners' understanding, and the need for harmonization across different Islamic legal schools and legal codification. Nonetheless, there is significant potential to align the substantive justice values of Islamic law with the national legal system through institutional strengthening and Islamic legal education. This article recommends a procedural law reform grounded in maqășid syarī ah to promote a more responsive, just, and contextually Islamic legal system in Indonesia.